Performance of Maize-Bean Intercropping Assessed Through Varied Spatial Arrangements and Nutrient Phosphorus Levels in Tanzania - Masele, Wilson; Kisetu, Eliakira; Faraja, Makwinja (Indonesian Journal of Agricultural Research, 2022)
Erratic climatic conditions, inherent low fertility and nutrient depletion are among the most important biophysical constraints of food crops production in semi-arid African regions. This study aimed to elucidate the impact of different crop spatial arrangements associated with different levels of Phosphorus on the performance of maize-bean intercropping in Tanzania. The experiment was laid in a complete randomized design of factorial-split arrangement and three factors in different levels. Sowing patterns were randomly assigned to all experimental plots whereas Phosphorus rates were randomly assigned within a specific sowing pattern one after another. Data were subjected to statistical analysis using GenStat software of a generalized treatment structure in a randomized design. Results of the interaction between cropping pattern and the P-rates on beans and maize at a 5% level of significance indicated that grain yield, pods/plant, and biological yield did not differ significantly (P>0.05) while plant height, leaf area index, and plants per plot differed significantly (P<0.05). Intercropping affects the growth and development of component crops depending on the cropping pattern and the nutrients applied. The choice of compatible crops for an intercropping system should not exempt growth habits of the crops, land size, light, water fertilizer utilization. and other agronomic practices.